LncRNA CRNDE triggers inflammation through the TLR3-NF-κB-Cytokine signaling pathway - Haowen Li; Qi Li; Tao Guo; Wenyan He; Chengya Dong; Yajie Wang (Tumor Biology, 2017)
Colorectal neoplasia differentially expressed (CRNDE), an oncogene, is highly expressed in many tumor cells and affects cellular proliferation, migration, invasion, and apoptosis. Its function and mechanism of action is a research hotspot. In this study, microarray analysis was performed to discover the differentially expressed genes in CRNDE over-expression cells. RT² Profiler PCR Array was used to study the expression of genes related to the toll-like receptor (TLR) pathway. We found that over-expression of CRNDE in astrocytes increased the expression of key factors in the toll-like receptor signaling pathway, especially toll-like receptor-3-mediated MyD88-independent pathway. Furthermore, it up-regulated expression levels of downstream transcription factor such as nuclear factor kappa B and numerous cytokines. In contrast, CRNDE knockdown in glioma U87MG cell line showed an opposite trend in the expression of the above-mentioned genes. We speculated that CRNDE might trigger inflammation to regulate tumorigenesis and tumor development through the toll-like receptor pathway.